Analysis Of Projected Employment Opportunities In The Productive Age Population In Malang City - Syafiq, Muhammad; Verdiyanata, Jimmi Febri (Badan Perencanaan Pembangunan Kota Malang, 2024)
Malang City is a reflection of economic and social dynamics in society, especially in the context of employment opportunities. Theabstract aims to analyze factors influencing employment opportunities in Malang City and propose strategies for improvement. Through descriptive and comparative analysis methods using data from Badan Pusat Statistik and relevant research, fluctuations in the labor market concerning education, employment-population ratio, and self-employed workforce proportion are examined. Results indicate significant fluctuations in employment due to external factors like the COVID-19 pandemic and economic recovery policies. Strategic measures suggested include curriculum revamps, enhancing vocational education quality, and digital infrastructure development to align skills with market demands. Collaboration among government, industry, and educational institutions is proposed to create new job opportunities. Integrating inclusive, sustainable, and participatory strategies could foster a more inclusive economic environment, providing broader employment opportunities for Malang City residents amidst globalization and increasing competition.